Influence of Innovation and Entrepreneurial Orientation on Competitive Through Marketing Performance as Moderating - Aprillia, Eka Melany (Marketing and Business Strategy, 2024)
This study aims to determine the direct influence of innovation and entrepreneurial orientation on competitive advantage with marketing performance as a moderating variable on handicraft MSME entrepreneurs in East Jakarta and the indirect effect of innovation on competitive advantage through marketing performance, the effect of entrepreneurial orientation on competitive advantage through marketing performance. The research strategy used is quantitative. The population in this study are SMEs registered with the Mayor of East Jakarta. The sampling technique used was purpose sampling with data collection instruments consisting of questionnaires. The data taken is primary data. This study uses Path Analysis. The results of the study concluded that innovation and entrepreneurial orientation have a direct effect on competitive advantage through marketing performance. For the mediating effect, marketing performance is not a variable that moderates innovation towards competitiveness excellence. Nevertheless, marketing performance fully moderates entrepreneurial orientation towards competitiveness excellence. The managerial implication of these findings is that MSMEs need to pay attention not only to aspects of innovation and entrepreneurial orientation in their strategy but also to the importance of marketing performance management.